2016
DOI: 10.3892/ijo.2016.3681
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 activity regulates sensitivity to tumor necrosis factor-related apoptosis-inducing ligand-induced apoptosis in cervical cancer cells

Abstract: In cervical cancer, p53-induced apoptosis is abrogated by human papilloma virus (HPV)-derived oncoprotein E6. Although tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) provides tumor-specific apoptosis in various cancers, including cervical cancer, the sensitivity differs depending on the cell lines. Signal transducer and activator of transcription 3 (STAT3) is a hub molecule that shifts the cellular fate to apoptosis or survival in response to cellular stresses. However, the contribution of STA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 49 publications
(58 reference statements)
0
12
1
Order By: Relevance
“…Multiple different genes including p53, BCL2, AKT2, and STAT3 have been reported to regulate apoptosis in cervical cancer (23,(32)(33)(34). The p53 family of proteins is central regulator of cell survival and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple different genes including p53, BCL2, AKT2, and STAT3 have been reported to regulate apoptosis in cervical cancer (23,(32)(33)(34). The p53 family of proteins is central regulator of cell survival and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that activated STAT3 suppresses p53-mediated apoptosis by binding to the promoter of p53 and inhibiting the transcription of p53. STAT3 can promote tumor cell proliferation by up-regulating the expression of the cyclinB1/cdc-2/c-myc/cyclinD1/c-jun/c-fos complex and down-regulating the expression of the cyclinB1 kinase inhibitor CDK1 in p21/p27 expressing cells, which drives rapid progression through the G1/S checkpoint 5961 .…”
Section: Stat3 Activation In Cancermentioning
confidence: 99%
“…9 We refer to the CD133 + CSCs in our study as "cancer stem-like cells" because although previous studies have reported that CD133 + cells from several human tumors exhibit xenotransplantation potential in severe combined immunodeficiency (SCID) mice, 10,11 isolated CD133 + cells from human RCC tissue failed to form tumors when transplanted into SCID mice but instead, these cells potentiate tumor engraftment when cotransplanted with CD133 -RCC cells. 13 STAT proteins can be tyrosine, serine, and/or threonine phosphorylated. Significantly, CD133 expression has been suggested as a useful risk stratification tool in RCC.…”
Section: Introductionmentioning
confidence: 99%
“…12 Signal transducers and activators of transcription (STAT) exist as latent, un-phosphorylated monomers in the cytoplasm, and transmit signals from diverse cytokines and growth factors. 13 STAT proteins can be tyrosine, serine, and/or threonine phosphorylated. 14 The best-known pathway involves the Janus kinase (JAK)-mediated phosphorylation of tyrosine residues, inducing STAT dimerization and translocation into the nucleus where phosphorylated (p)STATs act as transcription factors.…”
Section: Introductionmentioning
confidence: 99%